Red Dwarf. I [videorecording (DVD)] - Bye, Ed; Bye, Ed; Grant, Rob (Robert Ray); Naylor, Doug; Barrie, Chris, 1960-; Charles, Craig, 1964-; John-Jules, Danny; Lovett, Norman, 1946- (BBC Video, 2003)
This sitcom follows the exploits of Lister, a deep-space miner who emerges from stasis 3 million years in the future to find that his only companions are Rimmer, a hologram of his dead bunkmate, Cat, a humanoid who evolved from his pet cat, and Holly, the ship's computer.